Non-syngas direct steam reforming of methanol to hydrogen and carbon dioxide at low temperature. - Yu, K; Tong, W; West, A; Cheung, K; Li, T; Smith, G; Guo, Y; Tsang, S (2012)
A non-syngas direct steam reforming route is investigated for the conversion of methanol to hydrogen and carbon dioxide over a CuZnGaO(x) catalyst at 150-200 °C. This route is in marked contrast with the conventional complex route involving steam reformation to syngas (CO/H2) at high temperature, followed by water gas shift and CO cleanup stages for hydrogen production. Here we report that high quality hydrogen and carbon dioxide can be produced in a single-step reaction over the catalyst, with no detectable CO (below detection limit of 1 ppm). This can be used to supply proton exchange membrane fuel cells for mobile applications without invoking any CO shift and cleanup stages. The working catalyst contains, on average, 3-4 nm copper particles, alongside extremely small size of copper clusters stabilized on a defective ZnGa2O4 spinel oxide surface, providing hydrogen productivity of 393.6 ml g(-1)-cat h(-1) at 150 °C.